THE MAIN DIRECTIONS OF THE ENERGY DEVELOPMENT AT BELORUSSIAN METALLURGICAL WORKS - A. A. Sotnikov (Литьë и металлургия)
The review of technical decisions on using of utilization heat in the systems of air conditioning, sewage water clearing, keeping of constant oxygen pressure in the plant set at provision from three independent sources is reflected in the article. The cumulative experience of the sewage water clearing at the facilities of back osmosis is noted, the qualitative figures of sewage membranes of different kinds are analyzed. The carrying out of technical decisions will allow to decrease considerably the deleterious effect on the environment.